Methylomes of Two Extremely Halophilic Archaea Species, Haloarcula marismortui and Haloferax mediterranei - DasSarma, Shiladitya (Microbiol Resour Announc, 2019)
The genomes of two extremely halophilic Archaea species, Haloarcula marismortui and Haloferax mediterranei, were sequenced using single-molecule real-time sequencing. The ∼4-Mbp genomes are GC rich with multiple large plasmids and two 4-methyl-cytosine patterns. Methyl transferases were incorporated into the Restriction Enzymes Database (REBASE), and gene annotation was incorporated into the Haloarchaeal Genomes Database (HaloWeb).